Моделирование влияния условий получения композиционных ПСТМ из вюрцитного нитрида бора на их напряженно-деформированное состояние - Степаненко, А.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
Theoretical study of the level of residual stress in phase composite BNsf+BNv was investigated by the statistical theory. Stress-strain state of boron nitride composite depends on parameters of sintering. Level of residual stress in a composite obtained at the real conditions is high. Tensile stresses in BNsf and compressive stresses in BNv are ∼1.5 GPa and ∼1,1GPa correspondingly.